A Multi-Level Balance Model for an Inclusive and Sustainable Security Order in MENA - Dehshiri, Mohammad Reza; Ghorbani, Saeed; Moradi, Mohammad (Eximia, 2022)
From Morocco in the west to Afghanistan in the east, Middle East and North Africa (MENA) has always been a scene for many various security problems. Multi-dimensional type of security, high number of actors, exogenous approach of residents towards security, fragile order, and diversity of discourses are among key features adding to these security problems. To overcome the problem, researchers and analysts from around the world have, since years ago, suggested different security models to create a stable situation in the region. None of these suggestions have ever been a viable model for the restive region of MENA. Considering shortcomings of all previously suggested models and architectures offered to realize a security order in MENA, the current research paper suggests a new model which can form a sustainable security order in the region. This new model takes all the influential domestic and foreign actors as well as their interests into account and forms a multi-layer balance all over the region. This new model provides security for all members of the MENA based on the division of sphere of influence and division of important areas of economy, politics, and military among all significant players of the region. This mulit-level balance model gives a kind of dominance to every important player in one of the mentioned areas and spheres and it provides each member of the region with a specific jurisdiction. Subsequent elite and economy based ties will strengthen achieved security order; hence, a region-wide real peace and stability for the people.